Molecular mechanisms and therapeutic strategies of Naegleria fowleri Carter (1970): a review of the fatal brain-eating amoeba - N. Datta (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія)
Naegleria fowleri is a thermophilic free-living amoeba that can cause a rare and fatal infection of the brain called primary amoebic meningoencephalitis (PAM). PAM is a serious public health concern, as it affects mostly young and healthy individuals who are exposed to warm freshwater environments, and has a mortality rate of approximately 98%. The infection occurs when the amoeba enters the nasal cavity during swimming or other recreational activities, and migrates to the brain through the olfactory nerve. In the brain, the amoeba causes extensive tissue necrosis, haemorrhage, and inflammation, leading to severe neurological symptoms and death within days. The pathogenesis of N. fowleri infection is not fully elucidated, but recent studies have shed some light on the molecular mechanisms that enable the amoeba to invade, proliferate, and evade the host immune system. These mechanisms include the expression of various surface molecules that mediate adhesion, motility, and phagocytosis of host cells, as well as the secretion of proteases and other factors that degrade host extracellular matrix and modulate host immune response. However, there are still many unanswered questions regarding the complex interactions between the amoeba and its host, which limit the development of effective diagnostic and therapeutic strategies. PAM is often misdiagnosed as bacterial meningitis, due to its nonspecific clinical presentation and lack of reliable diagnostic tests. This results in delayed or inappropriate treatment and poor prognosis. Currently, there is no specific or approved treatment for PAM, and the available options are based on empirical evidence or case reports. The survival rate of PAM remains very low, despite the use of multiple drugs and supportive care. Therefore, there is an urgent need for more research on the pathogenesis of N. fowleri and the identification of novel targets for intervention. With the advances in genomic and proteomic technologies, new opportunities have emerged to explore the molecular biology of N. fowleri and its host response. By identifying the genes and proteins involved in key processes such as adhesion, motility, and immune evasion, researchers can design targeted therapies to disrupt these essential functions and prevent or treat infection. This review provides a comprehensive overview of the current state of knowledge on N. fowleri, its pathogenic molecular mechanisms, and the biological processes involved in its infection, as well as the challenges and perspectives for future research.